Inanimate Nature. Pondering the Reproductive Daguerretype - Batchen, Geoffrey (Artium Quaestiones, 2022)
Little has been published about reproductive daguerreotypes, a genre of photographic still life in which another picture – a drawing, an engraving, a lithograph, a painting, a printed text – is the sole referent. However, as this essay demonstrates, a study of reproductive daguerreotypes is a study of daguerreotypy itself – of its capacities and limitations as a medium, of its major figures and its diversity of commercial applications, of its many possible meanings, functions and related viewing practices. But it is also an opportunity to reflect on the place of such daguerreotypes in the larger story concerning the photographic reproduction of artworks. Reproductive daguerreotypes are distinctive in that they copy an artwork exactly but unfaithfully: they often laterally reverse the image even while rendering it small, monochrome, precious, shiny, evanescent, mobile. Most striking is the way such daguerreotypes partake of the logic of reproducibility without necessarily participating in the processes of mass production normally associated with it: as unique copies, they offer replication without multiplicity. In so doing, they complicate the orthodox account of this process promulgated by Walter Benjamin in the 1930s and repeated so many times since.